Kinesin heavy chain function in Drosophila glial cells controls neuronal activity. - Schmidt, I.; Thomas, S.; Kain, P.; Risse, B.; Naffin, E.; Klämbt, C. (Journal of Neuroscience, 2012)
Kinesin heavy chain (Khc) is crucially required for axonal transport and khc mutants show axonal swellings and paralysis. Here, we demonstrate that in Drosophila khc is equally important in glial cells. Glial-specific downregulation of khc by RNA interference suppresses neuronal excitability and results in spastic flies. The specificity of the phenotype was verified by interspecies rescue experiments and further mutant analyses. Khc is mostly required in the subperineurial glia forming the blood-brain barrier. Following glial-specific knockdown, peripheral nerves are swollen with maldistributed mitochondria. To better understand khc function, we determined Khc-dependent Rab proteins in glia and present evidence that Neurexin IV, a well known blood-brain barrier constituent, is one of the relevant cargo proteins. Our work shows that the role of Khc for neuronal excitability must be considered in the light of its necessity for directed transport in glia.